Fever year : the killer flu of 1918 : a tragedy in three acts - Brown, Don, 1949- (Houghton Mifflin Harcourt, 2019)
"New Year's Day, 1918. America has declared war on Germany and is gathering troops to fight. But there's something coming that is deadlier than any war. When people begin to fall ill, most Americans don't suspect influenza. The flu is known to be dangerous to the very old, young, or frail. But the Spanish flu is exceptionally violent. Soon, thousands of people succumb. Then tens of thousands ... hundreds of thousands and more. Graves can't be dug quickly enough. What made the influenza of 1918 so exceptionally deadly--and what can modern science help us understand about this tragic episode in history? With a journalist's discerning eye for facts and an artist's instinct for true emotion, Sibert Honor recipient Don Brown sets out to answer these questions and more in Fever Year."--Provided by publisher